Gene therapy for colorectal cancer. - Kerr, D; Seymour, L; Maruta, F (2003)
Colorectal cancer is an important public health problem worldwide. Gene therapy has therapeutic potential for patients with advanced or recurrent colorectal cancer, incurable by conventional treatments. To date, many strategies of gene therapy have been explored, including mutant gene correction, prodrug activation, immune stimulation and genetically-modified oncolytic viruses. Although the preclinical results of gene therapy for colorectal cancer have shown promise, gene therapy is still at an early stage of clinical development and has not yet shown a significant therapeutic benefit for patients. The main obstacles for introduction of gene therapy to patients are poor targeting selectivity of the vectors and inefficient gene transfer. As the science supporting tumour-selective vectors evolves, gene therapy may expand rapidly in the clinical practice of colorectal cancer treatment.